Comparison of sleep diary and actigraphy to evaluate total sleep time in hypersomnia patients. Issue 2 (28th January 2013) - Tomita, Satoe; Kitajima, Tsuyoshi; Mekata, Takahiro; Tsuchiya, Akiko; Sano, Wataru; Esaki, Yuichi; Marina, Hirose; Fujita, Shiho; Iwata, Nakao
Abstract A sleep diary is often employed for diagnosing and treating hypersomnia. However, its reliability needs to be evaluated because overlooked chronic sleep insufficiency could be misdiagnosed as narcolepsy. In this study, we compared simultaneous sleep measurements using a sleep diary and by actigraphy in patients visiting our sleep clinic for the first time with complaints of excessive daytime sleepiness. Of the 28 patients enrolled, 24 complied with both these requirements. In this population, the results obtained using a sleep diary tended to estimate a statistically significant earlier sleep onset time and longer total sleep time than those via actigraphy. For total sleep time, this tendency was more prominent in patients with a higher Epworth Sleepiness Scale score. In 5 of the 24 (20.8%) patients, the sleep diary records indicated >6 h of total sleep time while the actigraphy records indicated <6 h of total sleep time, with a discrepancy of >1 h. These results suggested that sleep insufficiency in hypersomnia patients may be overlooked when their sleep time is assessed using only a sleep diary in the initial phase of the diagnostic procedure, and the simultaneous use of actigraphy may be preferable in this assessment.